Green Data Science in Cyber Security: Network Security Threat Detection and Prevention Techniques - Rahim, Robbi; Thanh Nguyen, Phong; Nurwita, Nurwita; Laxmi Lydia, E.; Shankar, K. (Opción, 2019)
Nowadays a business models, supported the merchandise sales, to new product-service systems is chance for industrial corporations to realize and new advantage. Because it needs elementary changes within the structure, culture and competencies of the corporate and ne’er the less makers overtime fight with this innovation. Rarely, however industrial perceive they ought to reconfigure the weather of the business model (BM). Additionally, Product-Service System is a business models exten- sively and tiny support to the still offers and decision-making method relating to the service transformation. An application of the framework during a capital product manufacturer and supply analysis insights. The tools to work out the business model for any organization for the innovation of the business. The business model innovation for achieving profitable, growth of business model. Business models the method of the methodology to sensible, toolkit has been developed by the used of techniques. A business model produce, describe, creates, delivers and captures worth. The business model method is modification,operating and construction is named the business model innovation of the business strategy.